2013
DOI: 10.1002/cbm.1893
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal HCR‐20 scores in a high‐secure psychiatric hospital

Abstract: It is unsurprising that patients in two national services (for men with intellectual disability and women) have the highest HCR-20 scores; however, the finding of relatively greater risk reduction in women needs further investigation. Although we did not find ceiling effects in this sample, the clinical value of frequently repeated HCR-20 ratings may be limited for high-risk populations where any change is likely to be slow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
1
19
1
Order By: Relevance
“…Olsson et al (), for example, found reductions in scores on some items from the clinical and risk management scales after 9 months and on all but two risk items after a mean of 43 months. Morrissey et al () found that the mutable – clinical and risk management items – showed improvement over a 5‐year period in a high security hospital. These findings together suggest that the HCR‐20 is sensitive to change but over a longer period than the 6‐month and 12‐month period we adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olsson et al (), for example, found reductions in scores on some items from the clinical and risk management scales after 9 months and on all but two risk items after a mean of 43 months. Morrissey et al () found that the mutable – clinical and risk management items – showed improvement over a 5‐year period in a high security hospital. These findings together suggest that the HCR‐20 is sensitive to change but over a longer period than the 6‐month and 12‐month period we adopted.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews highlighted the utility and promise for including risk assessment tools, such as the Historical Clinical Risk‐20 (HCR‐20) (Webster et al, ), as an outcome measure as well as a tool for assisting assessment of risk of harm. A small, but significant, change in HCR‐20 scores over time on Clinical and Risk Management subscales and total scores has been shown in an English high security hospital sample (Morrissey et al, ) and in individual items on these subscales with level of security need as measured on a 9‐point scale (Müller‐Isberner et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Longer treatment times have been found to be associated with reduced scores on the clinical and risk-management scales (10,11) and mean scores reduce between the first and second HCR-20 assessments (12). Morrissey and colleagues (13) also found statistically significant reductions in dynamic items each year. However, across studies, average changes were small with total clinical scores reducing by 0.19 to 0.32 points and risk-management scores reducing by 0.14 to 0.31 points per iteration (12,13).…”
Section: Introductionmentioning
confidence: 95%
“…Most commonly, services used the structured clinical judgement tool the Historical, Clinical Risk 20 . 23,33,34,43,53,54,58,59 Other studies reported on static risk assessment measures such as the Violence Risk Appraisal Guide (VRAG), 23,53,54 Risk Matrix 2000, 53 Offender Group Reconviction Scale 22 and Static-99, 53 although these would not have utility as outcome measures as they would not be expected to change. The vast majority of these studies reported only cross-sectional data and not within-patient change in such measures over time.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The vast majority of these studies reported only cross-sectional data and not within-patient change in such measures over time. Indeed, only one study reported change in scores over 5 years on the clinical risk items of the HCR-20 as an outcome indicator in a FIDD service, 33 despite the large number of services that are required to collect routine data on this measure.…”
Section: Risk Assessmentmentioning
confidence: 99%